Causes of Hearing Impairment Observed in Clinical/Hospital Setting - Mehreen Babar, Fatima Usman, Wajih Ud Din Shinwari, Sajid Rashid Nagra, Salman Aftab Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Aim of current study was to determine the causes of hearing impairment among patients visited to hospital. Study Design: Observational study Place and Duration: Frontier medical college, Abbottabad, May, 2021 to April, 2022. Methods: Total 122 patients of both genders had complained of hearing impairment were included. After obtaining informed written consent detailed demographics were recorded. An extensive history, thorough E.N.T. examination, and pertinent radiological and audiological tests were performed. Frequency of causes for hearing impairment was assessed. SPSS 20.0 was used to analyzed all data. Results: Among all cases, 68 (55.7%) patients were males and 54 (44.3%) were females. Mean age of the patients was 17.5±11.50 years. 72 (59.02%) cases were from rural areas and 75 (61.5%) cases had poor socio-economic status. We found that conductive hearing loss was the most common found in 63 (51.6%) cases, followed by mixed hearing loss in 35 (28.7%) cases and sensorineural hearing loss found in 24 (19.7%) cases. Chronic Suppurative Otits Media was the most common cause of hearing impairment found in 61 (50%) cases, followed by infection, physical trauma, prenatal causes, postnatal causes, drug related and other problem. Conclusion: We concluded in this study that COSM was the most common cause of hearing impairment among all cases. Most common hearing loss was conductive, mixed and sensorineural. It is possible to reduce the incidence of sensorineural hearing loss by preventing variables that occur both during and after pregnancy. Keywords: Hearing Loss, Hearing Impairment, COSM, SNHL